Phase I Trial of Pegylated Liposomal Doxorubicin Combined with Ifosfamide for Advanced Soft Tissue Sarcoma - Ye T; Fan L; Cao R; Peng L; Chen J (Drug Design, Development and Therapy)
Ting Ye,1,2 Li Fan,1 Rubo Cao,1 Ling Peng,1 Jing Chen1,3 1Cancer Center, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 2Hubei Key Laboratory of Precision Radiation Oncology, Wuhan, 430022, People’s Republic of China; 3Institute of Radiation Oncology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of ChinaCorrespondence: Jing Chen, Email chenjingwh@hust.edu.cnIntroduction: This study aimed to determine the maximum tolerated dose (MTD) of pegylated liposomal doxorubicin (PLD) combined with both ifosfamide (IFO) and supported by human granulocyte colony-stimulating factor (rhG-CSF) for treating advanced soft tissue sarcoma (STS).Methods: Twenty-three patients were enrolled in this trial with 3+3 dose-escalation from January 2020 to September 2022. PLD was initiated at 30 mg/m2 and incrementally escalated by 5 mg/m2 per step. MTD was the primary endpoint, and the safety profile served as the secondary endpoint.Results: Two patients treated with PLD (55 mg/m2) experienced dose-limiting toxicities. Ultimately, the MTD of PLD was established as 50 mg/m2 (single cycle) in combination of IFO (3 g/m2/day for days 1– 3) and supported by rhG-CSF. Across all dose levels, common grade 3/4 adverse events included leukopenia (86.96%), neutropenia (82.61%), and lymphopenia (56.52%). Twelve of the 23 patients voluntarily chose to continue treatment with this regimen. The overall response rate was 33.33% (95% confidence interval: 9.92– 65.11), and the disease control rate was 83.33% (95% confidence interval: 51.59– 97.91).Conclusion: This study successfully determined the MTD of PLD in combination with IFO and rhG-CSF for advanced STS, offering a potentially valuable treatment option with a tolerable safety profile.Keywords: soft tissue sarcomas, pegylated liposomal doxorubicin, ifosfamide, dose-escalation, safety